On how women took over office work - Juul, Ida; Juul, Ida (Tidsskrift for Arbejdsliv, 2010)
The focus in this article is on the process through which gendered jobs are created. The hypothesis put forwarding is that the positioning of office work as respectable at the beginning of the 20th century made it an attractive occupation for unmarried middle-class women in the interim between leaving school and entering marriage. At the same time, office work in general became less attractive for men. From being an occupation with good career opportunities reserved for men from the upper and middle classes it became a temporary occupation for middle-class women, who, unlike their male colleagues, were not expected to obtain a certificate of completed apprenticeship. As office work expanded it also became accessible to the sons and daughters of skilled workers. The notion of respectability also played an important role in the political discourse connected to office work as it was promoted by the employers and their organisations in order to differentiate office work from skilled and unskilled jobs in industry and especially from the labour movement. The unions, on the other hand, fought to organize the office workers and appealed to their solidarity and identity as workers. This illustrates how different meanings were ascribed to office work and to women labour force. The article also shows how categories like class, gender, age and marital status intersected in different ways in different periods in order to exclude certain groups and include others in the office sector. Based on an analysis of two memoirs, the article illustrates how the ways we choose to perform gender interacts with the ways a given society at different times and in different contexts defines femininity and masculinity, and how a career as an office worker could be experienced differently depending on gender.